Answer:
Using point (-21, -22): y = (6/7)x - 4
Using point (-14, -16): y = (6/7)x - 4
Step-by-step explanation:
The point-slope form of a line's equation is:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
Where (x₁, y₁) is a point in the line and m is the slope.
The slope of a line can be calculated as:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
Where (x₁, y₁) and (x₂, y₂) are two points in the line. So, replacing (x₁, y₁) by (-21, -22) and (x₂, y₂) by (-14, -16), we get that the slope of the line is:
![m=(-16-(-22))/(-14-(-21))=(-16+22)/(-14+21)=(6)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/pim53bgboazm3abkwegp4o7qvs9bkoeeaj.png)
Now, using the point (-21, -22), we get that the equation of the line is:
![\begin{gathered} y-(-22)=(6)/(7)(x-(-21)) \\ y+22=(6)/(7)(x+21) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/liwubk4xg9gtk9d6rqpzq6phthsa7dva0n.png)
Then, we can simplify the equation as:
![\begin{gathered} y+22=(6)/(7)(x)+(6)/(7)(21) \\ y+22=(6)/(7)x+18 \\ y+22-22=(6)/(7)x+18-22 \\ y=(6)/(7)x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/729ct5yb3xufvyp1ir95idnvgq6p1yqile.png)
On the other hand, using the point (-14, -16), the equation of the line is:
![\begin{gathered} y-(-16)=(6)/(7)(x-(-14)) \\ y+16=(6)/(7)(x+14) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dq1ijawvcoprk09ycfzipgekwcakx6ewgo.png)
Simplifying, we get:
![\begin{gathered} y+16=(6)/(7)x+(6)/(7)(14) \\ y+16=(6)/(7)x+12 \\ y+16-16=(6)/(7)x+12-16 \\ y=(6)/(7)x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g1i95zes76gea4drb78woazk6wntmyr20q.png)
So, the answers are:
Using point (-21, -22): y = (6/7)x - 4
Using point (-14, -16): y = (6/7)x - 4